Study of polymer-based adhesive mortar with higher durability. Issue 1 (December 2021) - Hermann, R; Figala, P; Mészárosová, L; Drochytka, R
Abstract: This paper deals with the study and development of polymer-based adhesive with high filling ratio of secondary raw materials and waste materials. The goal of this paper is to develop adhesive mortar with the highest filling rate of secondary raw materials and waste materials as possible while preserving very high physical-mechanical properties, including flexural and compressive strength, pull-off bond strength and abrasion resistance. High-temperature fly ash, waste slag and waste packaging glass are used in this paper as fillers. The resulting mortar shows high physical-mechanical properties, including high abrasive resistance and very high bonding strength to a large variety of building materials including concrete, steel, glass, and tiles.